Endoderm-derived islet1-expressing cells differentiate into endothelial cells to function as the vascular HSPC niche in zebrafish - Nakajima, Hiroyuki; Ishikawa, Hiroyuki; Yamamoto, Takuya; Chiba, Ayano; Fukui, Hajime; Sako, Keisuke; Fukumoto, Moe; Mattonet, Kenny; Kwon, Hyouk-Bum; Hui, Subhra P.; Dobreva, Gergana; Kikuchi, Kazu; et al. (Developmental cell, 2023)
Endothelial cells (ECs) line blood vessels and serve as a niche for hematopoietic stem and progenitor cells (HSPCs). Recent data point to tissue-specific EC specialization as well as heterogeneity; however, it remains unclear how ECs acquire these properties. Here, by combining live-imaging-based lineage-tracing and single-cell transcriptomics in zebrafish embryos, we identify an unexpected origin for part of the vascular HSPC niche. We find that islet1 (isl1)-expressing cells are the progenitors of the venous ECs that constitute the majority of the HSPC niche. These isl1-expressing cells surprisingly originate from the endoderm and differentiate into ECs in a process dependent on Bmp-Smad signaling and subsequently requiring npas4l (cloche) function. Single-cell RNA sequencing analyses show that isl1-derived ECs express a set of genes that reflect their distinct origin. This study demonstrates that endothelial specialization in the HSPC niche is determined at least in part by the origin of the ECs.
Online verfügbar: 23. Januar 2023, Artikelversion: 6. Februar 2023
Gesehen am 30.09.2024